Lumbar spine fusion outcomes using a cellular bone allograft with lineage-committed bone-forming cells in 96 patients - Hossein Elgafy; Bradley Wetzell; Marshall Gillette; Hassan Semaan; Andrea Rowland; Christopher A. Balboa; Thomas A. Mierzwa; Julie B. McLean; Kimberly Dorsch; Mark A. Moore (BMC Musculoskeletal Disorders, 2021)
Abstract Background Instrumented posterior lumbar fusion (IPLF) with and without transforaminal interbody fusion (TLIF) is a common treatment for low back pain when conservative interventions have failed. Certain patient comorbidities and lifestyle risk factors, such as obesity and smoking, are known to negatively affect these procedures. An advanced cellular bone allograft (CBA) with viable osteogenic cells (V-CBA) has demonstrated high fusion rates, but the rates for patients with severe and/or multiple comorbidities remain understudied. The purpose of this study was to assess fusion outcomes in patients undergoing IPLF/TLIF using V-CBA with baseline comorbidities and lifestyle risk factors known to negatively affect bone fusion. Methods This was a retrospective study of de-identified data from consecutive patients at an academic medical center who underwent IPLF procedures with or without TLIF, and with V-CBA. Baseline patient and procedure characteristics were assessed. Radiological outcomes included fusion rates per the Lenke scale. Patient-reported clinical outcomes were evaluated via the Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for back and leg pain. Operating room (OR) times and intraoperative blood loss rates were also assessed. Results Data from 96 patients were assessed with a total of 222 levels treated overall (mean: 2.3 levels) and a median follow-up time of 16 months (range: 6 to 45 months). Successful fusion (Lenke A or B) was reported for 88 of 96 patients (91.7%) overall, including in all IPLF-only patients. Of 22 patients with diabetes in the IPLF+TLIF group, fusion was reported in 20 patients (90.9%). In IPLF+TLIF patients currently using tobacco (n = 19), fusion was reported in 16 patients (84.3%), while in those with a history of tobacco use (n = 53), fusion was observed in 48 patients (90.6%). Successful fusion was reported in all 6 patients overall with previous pseudarthrosis at the same level. Mean postoperative ODI and VAS scores were significantly reduced versus preoperative ratings. Conclusion The results of this study suggest that V-CBA consistently yields successful fusion and significant decreases in patient-reported ODI and VAS, despite patient comorbidities and lifestyle risk factors that are known to negatively affect such bony healing.